2023
DOI: 10.1002/rfc2.23
|View full text |Cite
|
Sign up to set email alerts
|

Research on vaginal dabbing: A systematic scoping review

Abstract: Introduction: Vabbing, also known as vaginal dabbing, is a known behaviour gaining ground in modern society. Vabbing is the act of dabbing vaginal secretions as body perfume droplets to sexually attract others. This study aims to conduct a scoping review (ScR) of empirical studies on vaginal dabbing. Methodology: This review, informed by the Joanna Brigg's Institute's guidelines for ScRs, was reported based on the Preferred Reporting Items for Systematic Reviews and Metanalysis for ScRs. Eight databases-PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Like other scoping reviews, 23 , 24 this current review seeks to answer this research question: what is the available evidence in Africa preventative interventions, by DCPs, on oral HPV, gonorrheal, chlamydial, syphilitic and trichomonas infections?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other scoping reviews, 23 , 24 this current review seeks to answer this research question: what is the available evidence in Africa preventative interventions, by DCPs, on oral HPV, gonorrheal, chlamydial, syphilitic and trichomonas infections?…”
Section: Methodsmentioning
confidence: 99%
“…In scoping reviews, data is extracted, collated, and summarized from the included literatures, provided they available. 23 , 24 However, this was not accomplished in this scoping review because no literature was found eligible for inclusion into the review. Hence, this is an empty scoping review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation